Oral focal mucinosis of gingiva - a rare case report and review of literature - Dabbiru, Chandini; Mahadev Naik, Raghavendra; Moturi, Kishore; Rajkumar, Govind (International Journal of Dental Research, 2017)
Oral focal mucinosis (OFM) is a rare soft-tissue lesion of unknown etiology. Clinically it appears as asymptomatic round lesions and histologically, characterized by focal myxoid degeneration of connective tissue with presence of stellate shaped fibroblasts which were also evident in the present case. This case report stresses on the fact that diagnosis of OFM is almost impossible hence diagnosis should be confirmed by histopathological examination following incisional or excisional biopsy. Through this article we present a rare case of one such lesion on the gingiva and enumerate the most characteristic and myxomatous lesions. Thus though rare, OFM must be considered in the differential diagnosis of soft tissue overgrowths in oral cavity. Here, we describe the clinical and histopathologicalÂ Â presentation and subsequent management of OFM in a female patient.